THE DIFFERENCE IN SITUATION EFFICIENCY OF GOALKEEPERS IN WINNING AND LOSEING TEAMS AT THE WORLD HANDBALL CHAMPIONSHIP FOR JUNIOR WOMEN IN KOREA - Dinko Vuleta (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The goal of this research is to analyze the differences in parameters of situation efficiency between the goalkeepers of the winning and losing teams on the end result of the handball match defined by the criteria win/loss (POB/POR). The sample of variables consists of frequencies of successful and unsuccessful saves made by the goalkeepers of the winning and losing teams. This research is conducted on a sample of 94 played games (188 opponents) of the World handball championship for junior women in Korea 2010. The participating (24 teams), were divided into four groups of six national teams. To determine success/failure in made saves the standard indicators of situation efficiency of goalkeepers were used. To determine the statistically significant differences between the variables the Mann-Whitney U test was used. In the variables saved shots from 9 meter positions successfully, saved shots from 6 meter positions unsuccessfully, saved shots from wing positions successfully, saved shots from wing positions unsuccessfully, saved shots from counter attacks successfully, saved shots from counter attacks unsuccessfully, and saved shots from breakthroughs unsuccessfully a statistically significant difference was determined at the level (p. ‹0.01) between winning and losing teams.